(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
This article presents a brief description of the housing and utilities sector in Russia. The assessment of the main financial indicators of enterprises for managing the operation of the housing stock in dynamics for 2017-2019 was carried out, as well as conclusions about the investment attractiveness of this area of economic activity for Russian investors.